PERSEPSI PUBLIK DAN MEDIA SOSIAL DALAM KAMPANYE DIGITAL PILPRES 2024 - Revolusi, Prabunindya Revta (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research in-depth explores the impact of political social media on the 2024 Indonesian presidential election process, especially concentrating on three candidates: Prabowo Subianto, Ganjar Pranowo, and Anies Baswedan. The study found that social media has become a highly effective tool for political campaigns, allowing candidates to reach young voters and influence overall public opinion. The content presented and the delivery methods each candidate chooses are key to the success of a digital campaign. The issues raised in the campaign are a representation of the needs, hopes and challenges faced by Indonesian society today. Plus, digital literacy is very important for analyzing information conveyed via social media. This study shows changes in political campaign strategies through public participation in the democratic process through two-way communication facilitated by social media. Emphasis on content and delivery methods is the key to successful digital campaigns. The issues raised reflect the needs, hopes and challenges of Indonesian society today, while digital literacy is important in analyzing the information presented. Social media provides space for active community participation in the democratic process by facilitating two-way communication, demonstrating adaptation and innovation in campaign strategies. Understanding how information is disseminated and received by the public has become increasingly important in politics increasingly influenced by social media. The stage of the art in this research is important in understanding how presidential elections take place in the technological era and provides strategic suggestions for future political campaigns. By connecting public perception and social media in the digital campaign for the 2024 presidential election, this research is important in shaping the direction of political debate and policy in Indonesia